Evaluation of Phonon Dispersion Relation for Bulk Silicon Germanium by Inelastic X-ray Scattering. (8th September 2020) - Yokogawa, Ryo; Takeuchi, Haruki; Arai, Yasutomo; Yonenaga, Ichiro; Uchiyama, Hiroshi; Ogura, Atsushi
Abstract : We report on phonon dispersion curves of bulk silicon germanium (Si1- x Ge x ) alloy with the x value of 0.16, 0.32, 0.45, and 0.72 obtained by inelastic x-ray scattering (IXS) with synchrotron radiation. All phonon dispersion relations of optical (Ge-Ge, Si-Ge, Si-Si modes) and acoustic modes were observed along the Γ-X ([00q]) direction obtained by energy positions of IXS spectra. The phonon dispersion curves of bulk Si1- x Ge x showed behaviors similar to those of pure Si and Ge. We also confirmed Ge fraction dependence of acoustic modes and revealed that the acoustic phonon energies are located between those of pure Si and Ge. From the above, it has been suggested that low thermal conductivity of SiGe alloy may contribute to phonon lifetime rather than group velocity.